Cutting-edge assessment techniques for B cell immune memory: an overview - Martina Bozhkova; Petya Gardzheva; Vanya Rangelova; Hristo Taskov; Marianna Murdjeva (Biotechnology & Biotechnological Equipment)
The adaptive humoral immune response depends on B cells. After antigens are processed and presented to naive B cells, these B cells differentiate into either surface immunoglobulin-expressing memory B cells (MBCs) or antibody-secreting plasma cells (PC) and long-lived plasma cells (LLPC). In parallel with the detection of antibodies, the detection of MBCs and LLPC is important to assess the strength and duration of the humoral immune response. The number of antigen-specific cells can be determined by the secretion of antibodies using highly sensitive techniques such as ELISpot or FluoroSpot. Flow cytometry is usually used to determine the antigen-specific MBC, PC and LLPC by binding of antigens to their surface immunoglobulins. In this technique, the antigen is either directly labelled with a fluorochrome or non-covalently linked to labelled streptavidin in a tetramer. The advantage of flow cytometry is that detailed phenotypic analysis of B cell subpopulations can be performed. Single-cell RNA Sequencing provides in-depth information about B-cell receptor diversity, functional states, transcriptomic changes associated with rare cell populations or dynamic cellular processes within the immune system. Additionally, it can lead to the discovery of novel B cell subsets previously unknown. The advantages, disadvantages and potential applications of each technique are thoroughly outlined. This overview of current knowledge on B-cell immune memory highlights some implications for advancing vaccination strategies, autoimmune disease management and personalized medicine.